Intelligence and security informatics : Pacific Asia Workshop, PAISI 2013, Beijing, China, August 3, 2013. Proceedings - Zheng, Xiaolong; Chau, Michael; Chen, Hsinchun; Wang, G. Alan (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2013, held in Beijing, China, in August 2013 in conjunction with the International Joint Conference on Artificial Intelligence (IJCAI 2013). The 4 revised full papers presented together with 7 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on information sharing and data/text mining; terrorism informatics; network-based data analytics; and information access and security.